Trends in Disseminating Audio on Demand Content through Podcast: An Opportunity and Challenge in Indonesia - Zellatifanny, Cut Medika (Jurnal Pekommas, 2020)
In the last two years, there has been a significant increase in access to audio on-demand content in Indonesia. The current trend of content dissemination is no longer centered on video-based content such as Youtube but has penetrated audio-based content such as Podcasts. One of the causes of podcasts' interest is the nature of flexibility that allows the audience to listen to audio content while doing other activities. This study aims to analyze the opportunities and challenges of podcasts in Indonesia and present them comprehensively. The method used in this research is literature review which includes the process of reading, sorting, and analyzing articles in journals, reference books, previous research reports, and news related to podcasts. The results of the study concluded that the emergence of trends in the distribution of audio-on-demand content through podcasts could create several opportunities that can be useful for its users in Indonesia, including podcasts that can be a medium for providing information to open new insights and thoughts, podcast also capable in produce more personal content, it can be used as an alternative media to disseminate audio content, it has significant opportunities for monetization, can complement conventional radio and video-based platforms, and has opportunities to be accessed safely and comfortably because of relatively small bandwidth requirements. In addition to opportunities, podcast development cannot be separated from various challenges, including competition with video-based content that has been popular among millennials, challenges in measuring and applying podcast monetization methods, challenges in production aspects, audio quality and optimizing content duration. Last but not least, challenges related to listener experience (LX)